Skeletal effects of mini-implant assisted rapid palatal expansion (MARPE) on the sagittal dimensions of the maxilla an in-vivo cone-beam computed tomography (CBCT) study - vairagi, DR Shymal; HEGDE, 2 DR ASHWITH; KALIA, 3 DR AJIT; NENE, 4 DR SALIL; RAJA, DR AMIT (South European Journal of Orthodontics and Dentofacial Research (SEJODR), 2021)
Introduction -Transverse discrepancies of the maxilla are one of the most prevalent skeletal problems. Due to drawbacks of conventional RPE and invasive surgical expansion methods alternative methods were developed such as Mini Implant-supported rapid maxillary expansion (MARPE).Haas17 , Davis and Kronman18, Akkaya et al19 and many other studies have reported the maxillary response after MARPE on the sagittal dimensions, but their results were inconclusive.Aim - This study analyzed the effects on the maxilla in the sagittal dimension after Mini Implant assisted rapid palatal expansion (MARPE) in adolescents using CBCT.Material and method -A pretreatment CBCT image (T1) was taken as a standard initial record for all patients and post treatment CBCT (T2) was taken after three months in retention. The parameters SNA angle, Frankfort horizontal plane to NA angle, A-N perpendicular, ANS –PNS were measured and calculated for evaluation of the sagittal maxillary changes. Comparisons were then made between the two treatment groups (T1, T2).Result -There was a positive increase in both angular and linear measurements from pretreatment to post treatment measurements showing significant skeletal changes in sagittal dimension.Conclusion -The study concludes that there was statistically significant forward displacement of maxilla after transverse skeletal expansion in patients with transverse problems achieved through MARPE in adolescent patients.